RELATIONSHIP BETWEEN FINANCIAL FAILURE AND PERFORMANCE: A RESEARCH ON BORSA ISTANBUL COMPANIES - GÜROL , Burcu; ÖZPARLAK, Gerçek (SSD Journal, 2022)
Financial failure refers to the situation in which the company changes or terminates its activities due to the inability to fulfil its financial obligations. Many studies have been carried out in order to predict this undesirable situation. Various models have been created in accounting-based studies using financial ratios. The most widely used of these models are Altman (1968), Springate (1978), Ohlson (1980), Fulmer (1984), Zmijewski (1984) and Grover (2001). The results obtained by using these models are followed by many stakeholders and accepted as the risk indicator of the enterprise. In this study, the relationship between the financial failure scores of 39 companies traded in the industrial sector in Borsa Istanbul between 2017 and 2021 and their market performance is analyzed separately. As a result of the study, it is seen that there is a positive and significant relationship between the Z-score value of the Altman (1968) model, which is an accounting-based financial failure model, and the Market Value/Book Value (M/B) ratio, which is a market-based performance indicator. These results show that investors invest more in companies with a low risk of financial failure since an increase in the Z-score means a decrease in the probability of financial failure of the business. However, in the research, no significant relationship is found between the scores of other financial failure models and the market-based indicator M/B.